2021
DOI: 10.1055/s-0040-1721787
|View full text |Cite
|
Sign up to set email alerts
|

Is Standing Coronal Long-Leg Alignment View Effective in Predicting the Extent of Medial Soft Tissue Release in Varus Deformity during Total Knee Arthroplasty?

Abstract: The aim of this study was to assess the predictive value of the femoral intermechanical-anatomical angle (IMA), mechanical lateral distal femoral angle (mLDFA), medial proximal tibia angle (MPTA), femorotibial or varus angle (VA), and joint line convergence angle (CA) in predicting the stage of the medial collateral ligament (MCL) during total knee arthroplasty (TKA) of varus knee. We evaluated 229 patients with osteoarthritic varus knee who underwent primary TKA, prospectively. They were categorized in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The multiple regression analyses in the present study showed that smaller MPTA is accompanied by smaller %MA with valgus stress and amount of %MA change. Sajjadi et al reported that there was a relationship between the extent of medial soft tissue release and small MPTA for medial‐lateral ligament balancing during TKA [24]. In addition, Shetty et al showed that small MPTA in healthy knees is associated with constitutional varus alignment [28].…”
Section: Discussionmentioning
confidence: 99%
“…The multiple regression analyses in the present study showed that smaller MPTA is accompanied by smaller %MA with valgus stress and amount of %MA change. Sajjadi et al reported that there was a relationship between the extent of medial soft tissue release and small MPTA for medial‐lateral ligament balancing during TKA [24]. In addition, Shetty et al showed that small MPTA in healthy knees is associated with constitutional varus alignment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to achieve soft tissue balance may lead to complications such as restricted range of motion (ROM), pain, and instability, possibly necessitating revision surgery [11][12][13]. Researchers have proposed various methods to achieve soft tissue balance, but the most accurate method has not yet been established [14][15][16][17][18]. The selection of an appropriate polyethylene (PE) insert thickness is one such approach based on the assessment of soft tissue tension and joint stability during TKA [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%